2020
DOI: 10.1155/2020/6403012
|View full text |Cite
|
Sign up to set email alerts
|

KIF15 Promotes Proliferation and Growth of Hepatocellular Carcinoma

Abstract: Liver cancer is thought as the most common human malignancy worldwide, and hepatocellular carcinoma (HCC) accounts for nearly 90% liver cancer. Due to its poor early diagnosis and limited treatment, HCC has therefore become the most lethal malignant cancers in the world. Recently, molecular targeted therapies showed great promise in the treatment of HCC, and novel molecular therapeutic targets is urgently needed. KIF15 is a microtubule-dependent motor protein involved in multiple cell processes, such as cell d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 35 publications
(43 reference statements)
0
7
0
Order By: Relevance
“…Knockdown using siRNA and overexpression of KIF4A resulted in attenuation and promotion of proliferation of HCC cell lines, respectively [ 36 ]. Knockdown of KIF15 by shRNA suppressed proliferation of HCC cell lines in vitro and in mice [ 37 ]. Recent studies reported that an increased expression of KIF4A and KIF15 are potential prognostic factors in prostate cancer [ 38 ] and lung adenocarcinoma [ 39 ], respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Knockdown using siRNA and overexpression of KIF4A resulted in attenuation and promotion of proliferation of HCC cell lines, respectively [ 36 ]. Knockdown of KIF15 by shRNA suppressed proliferation of HCC cell lines in vitro and in mice [ 37 ]. Recent studies reported that an increased expression of KIF4A and KIF15 are potential prognostic factors in prostate cancer [ 38 ] and lung adenocarcinoma [ 39 ], respectively.…”
Section: Discussionmentioning
confidence: 99%
“…During cell division, dysregulation of KIF15 can result in aberrant cell proliferation, tumorigenesis, and tumor aggressiveness (11). Recently, KIF15 has been proven to be over-expressed in various cancers including gastric cancer, hepatocellular carcinoma, and lung adenocarcinoma (12)(13)(14). However, the functions of KIF15 in pan-cancer are not fully understood.…”
Section: Introductionmentioning
confidence: 99%
“…Kif15 may also have uncharacterized roles in other aspects of kinetochore-microtubule attachment, suggested by data showing that overexpression of Kif15 results in lagging chromosomes (Malaby et al, 2019). In this light, it is notable that Kif15 is upregulated in a number of cancers (Ma et al, 2014;Wang et al, 2017;Qiao et al, 2018;Yu et al, 2019;Zhao et al, 2019;Sun et al, 2020;Terribas et al, 2020). Under normal circumstances, however, Kif15 localizes predominantly to k-fiber microtubules.…”
Section: Introductionmentioning
confidence: 99%